The kinetics of mycolactone in relation to the microbiological, clinical and immunological responses to antibiotic therapy for mycobacterium ulcerans disease. - Sarfo, Fred Stephen (2014)
A thesis submitted to the Department of Microbiology, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Microbiology